Association of vascular access flow with short-term and long-term mortality in chronic haemodialysis patients: a retrospective cohort study. Issue 9 (24th September 2017) - Wu, Chung-Kuan; Wu, Chia-Lin; Lin, Chia-Hsun; Leu, Jyh-Gang; Kor, Chew-Teng; Tarng, Der-Cherng
Abstract : Objectives: To investigate the impact of vascular access flow (Qa) on vascular and all-cause mortality in chronic haemodialysis (HD) patients. Design: Observational cohort study. Setting: Single centre. Participants: Adult chronic HD patients at the HD unit of Shin Kong Wu Ho-Su Memorial Hospital between 1 January 2003 and 31 December 2003 were recruited. Patients were excluded if they had arteriovenous fistula or arteriovenous graft failure within 3 months before the date of Qa measurement, were aged <18 years and had Qa levels of ≥2000mL/min. A total of 378 adult chronic HD patients were eventually enrolled for the study. Interventions: The selected patients were evaluated with Qa and cardiac index (CI). They were divided into four groups according to three Qa cut-off points (500, 1000 and 1500 mL/min). Primary and secondary outcome measures: Short-term and long-term vascular (cardiovascular or cerebrovascular) and all-cause mortality. Results: Qa was positively correlated with CI ( r =0.48, p<0.001). A Qa level of <1000 mL/min was independently associated with 1-year all-cause mortality (adjusted OR, 6.04; 95% CI 1.64 to 22.16; p=0.007). Kaplan-Meier analysis revealed that the cumulative incidence rates of all-cause and vascular mortality were significantly higher in the patients with a Qa level of <1000 mL/min (log-rank test; all p<0.01). Furthermore, a Qa level of <1000 mL/min was independently associated with long-term all-cause mortality (adjusted HR, 1.62; 95% CI 1.11 to 2.37; p=0.013); however, the risk of vascular mortality did not significantly increase after adjustment for confounders. Conclusions: Qa is moderately correlated with cardiac function, and a Qa level of <1000 mL/min is an independent risk factor for both short-term and long-term all-cause mortality in chronic HD patients.